Optimisation of moderator and neutron guide design for prompt gamma neutron activation analysis (PGNAA) using MCNP5 simulation [electronic resource] - Mazni Mohamed Johan, 1987-; Noorddin Ibrahim (2013)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2013